Band structure regulation in Fe-doped MgZnO by initial magnetic moments. Issue 6 (14th January 2021) - Zheng, Licheng; Yao, Qi; Wang, Hao; Zhan, Huahan; Cai, Wenwei; Zhou, Yinghui; Kang, Junyong
Abstract : The optoelectronic and magnetic properties of Fe-doped MgZnO are regulated by the Fe dopant and its initial magnetic moments. Abstract : ZnO-based diluted magnetic semiconductors have high prospects in spintronics applications. In this study, the electronic and magnetic properties of Fe-doped MgZnO are studied by density functional theory calculations. The investigations of the band structure, total density of states, and projected density of states revealed a strong correlation between Mg and O atoms in addition to the magnetism and impurity level generated by the Fe atoms. In the spin charge density and band structure of 2.78% Fe-doped MgZnO, Fe atoms always cause paramagnetic coupling with oxygen atoms bonded around them, and when the initial magnetic moments were parallel, the band gap is broadened in the opposite channel. On the contrary, when the initial magnetic moments are anti-parallel, the band gap is narrowed in both the spin-up and spin-down channels. This shows that the initial magnetic moments have a great influence on the band structure, giving another way to tune the gap dynamically.